Accelerating the National Implementation of Electronic Health Records in Canada - Francois, Monique J.; Obisike, Ebere Ellison (European Scientific Journal, ESJ, 2016)
Trends such as the aging population, long wait times, rising costs, and labour shortages in health professions are notable challenges facing the sustainability of Medicare in Canada. Healthcare reform, especially in primary care, will ensure efficiency and equitable access to healthcare in. Information and communication technologies (ICTs) such as electronic health records (EHRs) will play a pivotal role in reforming and sustaining Medicare. EHRs make healthcare safer, cost efficient and more integrated, and are necessary for the wider application of ICTs in the health sector. EHRs enhance decision-making capabilities for both providers and patients, especially in managing chronic diseases. Notwithstanding the numerous advantages of EHRs, Canada is slow to adopt a nation-wide EHR system. This paper analyzed existing data to establish the factors that may help to accelerate the national implementation of electronic health records in Canada. It defined EHRs, discussed their advantages and disadvantages, and barriers to its full application. Also, it explored key strategies for accelerating EHR initiatives in Canada, and suggested action plans and time frames for doing so.